5.1.39 Problems 3801 to 3900

Table 5.77: First order ode

#

ODE

Mathematica

Maple

7737

\[ {}y^{\prime } = 2 \sqrt {y} \]

7738

\[ {}y^{\prime } = 2 \sqrt {y} \]

7739

\[ {}y^{\prime } = \frac {x +y}{x -y} \]

7740

\[ {}y^{\prime } = \frac {y^{2}}{x y+x^{2}} \]

7741

\[ {}y^{\prime } = \frac {y^{2}+x y+x^{2}}{x^{2}} \]

7742

\[ {}y^{\prime } = \frac {y+x \,{\mathrm e}^{-\frac {2 y}{x}}}{x} \]

7743

\[ {}y^{\prime } = \frac {x -y+2}{x +y-1} \]

7744

\[ {}y^{\prime } = \frac {2 x +3 y+1}{x -2 y-1} \]

7745

\[ {}y^{\prime } = \frac {x +y+1}{2 x +2 y-1} \]

7746

\[ {}y^{\prime } = \frac {\left (x +y-1\right )^{2}}{2 \left (x +2\right )^{2}} \]

7747

\[ {}2 x y+\left (x^{2}+3 y^{2}\right ) y^{\prime } = 0 \]

7748

\[ {}x^{2}+x y+\left (x +y\right ) y^{\prime } = 0 \]

7749

\[ {}{\mathrm e}^{x}+{\mathrm e}^{y} \left (1+y\right ) y^{\prime } = 0 \]

7750

\[ {}\cos \left (x \right ) \cos \left (y\right )^{2}-\sin \left (x \right ) \sin \left (2 y\right ) y^{\prime } = 0 \]

7751

\[ {}x^{2} y^{3}-x^{3} y^{2} y^{\prime } = 0 \]

7752

\[ {}x +y+\left (x -y\right ) y^{\prime } = 0 \]

7753

\[ {}2 y \,{\mathrm e}^{2 x}+2 x \cos \left (y\right )+\left ({\mathrm e}^{2 x}-x^{2} \sin \left (y\right )\right ) y^{\prime } = 0 \]

7754

\[ {}3 \ln \left (x \right ) x^{2}+x^{2}+y+x y^{\prime } = 0 \]

7755

\[ {}2 y^{3}+2+3 y^{2} y^{\prime } x = 0 \]

7756

\[ {}\cos \left (x \right ) \cos \left (y\right )-2 \sin \left (x \right ) \sin \left (y\right ) y^{\prime } = 0 \]

7757

\[ {}5 y^{2} x^{3}+2 y+\left (3 x^{4} y+2 x \right ) y^{\prime } = 0 \]

7758

\[ {}{\mathrm e}^{y}+x \,{\mathrm e}^{y}+x \,{\mathrm e}^{y} y^{\prime } = 0 \]

7773

\[ {}y^{\prime } = 2 x \]

7774

\[ {}x y^{\prime } = 2 y \]

7775

\[ {}y y^{\prime } = {\mathrm e}^{2 x} \]

7776

\[ {}y^{\prime } = k y \]

7779

\[ {}x y^{\prime }+y = y^{\prime } \sqrt {1-x^{2} y^{2}} \]

7780

\[ {}x y^{\prime } = y+x^{2}+y^{2} \]

7781

\[ {}y^{\prime } = \frac {x y}{x^{2}+y^{2}} \]

7782

\[ {}2 x y y^{\prime } = x^{2}+y^{2} \]

7783

\[ {}x y^{\prime }+y = x^{4} {y^{\prime }}^{2} \]

7784

\[ {}y^{\prime } = \frac {y^{2}}{x y-x^{2}} \]

7785

\[ {}\left (y \cos \left (y\right )-\sin \left (y\right )+x \right ) y^{\prime } = y \]

7786

\[ {}1+y^{2}+y^{\prime } y^{2} = 0 \]

7787

\[ {}y^{\prime } = {\mathrm e}^{3 x}-x \]

7788

\[ {}y^{\prime } = x \,{\mathrm e}^{x^{2}} \]

7789

\[ {}\left (1+x \right ) y^{\prime } = x \]

7790

\[ {}\left (x^{2}+1\right ) y^{\prime } = x \]

7791

\[ {}\left (x^{2}+1\right ) y^{\prime } = \arctan \left (x \right ) \]

7792

\[ {}x y^{\prime } = 1 \]

7793

\[ {}y^{\prime } = \arcsin \left (x \right ) \]

7794

\[ {}\sin \left (x \right ) y^{\prime } = 1 \]

7795

\[ {}\left (x^{3}+1\right ) y^{\prime } = x \]

7796

\[ {}\left (x^{2}-3 x +2\right ) y^{\prime } = x \]

7797

\[ {}y^{\prime } = x \,{\mathrm e}^{x} \]

7798

\[ {}y^{\prime } = 2 \sin \left (x \right ) \cos \left (x \right ) \]

7799

\[ {}y^{\prime } = \ln \left (x \right ) \]

7800

\[ {}\left (x^{2}-1\right ) y^{\prime } = 1 \]

7801

\[ {}x \left (x^{2}-4\right ) y^{\prime } = 1 \]

7802

\[ {}\left (1+x \right ) \left (x^{2}+1\right ) y^{\prime } = 2 x^{2}+x \]

7803

\[ {}y^{\prime } = 2 x y+1 \]

7805

\[ {}y^{\prime } = \frac {2 x y^{2}}{1-x^{2} y} \]

7807

\[ {}x^{5} y^{\prime }+y^{5} = 0 \]

7808

\[ {}y^{\prime } = 4 x y \]

7809

\[ {}y^{\prime }+y \tan \left (x \right ) = 0 \]

7810

\[ {}\left (x^{2}+1\right ) y^{\prime }+1+y^{2} = 0 \]

7811

\[ {}y \ln \left (y\right )-x y^{\prime } = 0 \]

7812

\[ {}x y^{\prime } = \left (-4 x^{2}+1\right ) \tan \left (y\right ) \]

7813

\[ {}y^{\prime } \sin \left (y\right ) = x^{2} \]

7814

\[ {}y^{\prime }-y \tan \left (x \right ) = 0 \]

7815

\[ {}x y y^{\prime } = y-1 \]

7816

\[ {}x y^{2}-x^{2} y^{\prime } = 0 \]

7817

\[ {}y y^{\prime } = 1+x \]

7818

\[ {}x^{2} y^{\prime } = y \]

7819

\[ {}\frac {y^{\prime }}{x^{2}+1} = \frac {x}{y} \]

7820

\[ {}y^{\prime } y^{2} = x +2 \]

7821

\[ {}y^{\prime } = x^{2} y^{2} \]

7822

\[ {}\left (1+y\right ) y^{\prime } = -x^{2}+1 \]

7825

\[ {}y^{\prime }-x y = 0 \]

7826

\[ {}y^{\prime }+x y = x \]

7827

\[ {}y^{\prime }+y = \frac {1}{1+{\mathrm e}^{2 x}} \]

7828

\[ {}y^{\prime }+y = 2 x \,{\mathrm e}^{-x}+x^{2} \]

7829

\[ {}2 y-x^{3} = x y^{\prime } \]

7830

\[ {}y^{\prime }+2 x y = 0 \]

7831

\[ {}x y^{\prime }-3 y = x^{4} \]

7832

\[ {}\left (x^{2}+1\right ) y^{\prime }+2 x y = \cot \left (x \right ) \]

7833

\[ {}y^{\prime }+y \cot \left (x \right ) = 2 x \csc \left (x \right ) \]

7834

\[ {}y-x +x y \cot \left (x \right )+x y^{\prime } = 0 \]

7835

\[ {}y^{\prime }-x y = 0 \]

7836

\[ {}y^{\prime }-2 x y = 6 x \,{\mathrm e}^{x^{2}} \]

7837

\[ {}y^{\prime } x \ln \left (x \right )+y = 3 x^{3} \]

7838

\[ {}y^{\prime }-\frac {y}{x} = x^{2} \]

7839

\[ {}y^{\prime }+4 y = {\mathrm e}^{-x} \]

7840

\[ {}x^{2} y^{\prime }+x y = 2 x \]

7841

\[ {}x y^{\prime }+y = y^{3} x^{4} \]

7842

\[ {}y^{2} y^{\prime } x +y^{3} = x \cos \left (x \right ) \]

7843

\[ {}x y^{\prime }+y = x y^{2} \]

7844

\[ {}y^{\prime }+x y = y^{4} x \]

7845

\[ {}\left ({\mathrm e}^{y}-2 x y\right ) y^{\prime } = y^{2} \]

7846

\[ {}-x y^{\prime }+y = y^{\prime } y^{2} {\mathrm e}^{y} \]

7847

\[ {}x y^{\prime }+2 = x^{3} \left (y-1\right ) y^{\prime } \]

7848

\[ {}x y^{\prime } = 2 x^{2} y+y \ln \left (x \right ) \]

7849

\[ {}y^{\prime } \sin \left (2 x \right ) = 2 y+2 \cos \left (x \right ) \]

7850

\[ {}\left (x +\frac {2}{y}\right ) y^{\prime }+y = 0 \]

7851

\[ {}\sin \left (x \right ) \tan \left (y\right )+1+\cos \left (x \right ) \sec \left (y\right )^{2} y^{\prime } = 0 \]

7852

\[ {}y-x^{3}+\left (x +y^{3}\right ) y^{\prime } = 0 \]

7853

\[ {}2 y^{2}-4 x +5 = \left (4-2 y+4 x y\right ) y^{\prime } \]

7854

\[ {}y+y \cos \left (x y\right )+\left (x +x \cos \left (x y\right )\right ) y^{\prime } = 0 \]

7855

\[ {}\cos \left (x \right ) \cos \left (y\right )^{2}+2 \sin \left (x \right ) \sin \left (y\right ) \cos \left (y\right ) y^{\prime } = 0 \]

7856

\[ {}\left (\sin \left (x \right ) \sin \left (y\right )-x \,{\mathrm e}^{y}\right ) y^{\prime } = {\mathrm e}^{y}+\cos \left (x \right ) \cos \left (y\right ) \]